(untitled) (American Journal of Islam and Society, 2009)
This work examines the negotiations that Indonesian Muslim women have made in certain areas of life in the post-Suharto era, an era of socio-political reform in which “it is possible to question accepted attitudes and break new ground” (p. 16), and their religious practices and identities. The editors claim that their work breaks new ground in that (a) it informs readers of “how the women themselves experience their religion and actively engage with it in their lives” (p. 1); (b) it focuses on women and Islam in the post- Suharto period, in which Islam is more prominent and it is more acceptable to put forward feminist views in Indonesia and within Islam; and (c) it is the effort of insiders – Indonesian women with western and Islamic training – who can bridge the gap between western and Indonesian scholarship on Islam and women. The editors state up front that the book does not deliberately engage in a critical feminist theory and that they are not feminist writers; rather, they are influenced by feminism and desire to show that women are active participants and not mere “passive victims of male oppression” (p. 2) ...